PENGARUH PENERAPAN MODEL PEMBELAJARAN GIVING QUESTIONS AND GETTING ANSWER TERHADAP HASIL BELAJAR SISWA KELAS X SMA N BANYUDONO TAHUN AJARAN 2011/2012 - Chasanah, Amalia; Santosa, Slamet; Ariyanto, Joko (Pendidikan Biologi, 2012)
ABSTRACT ? This research is  aimed  to know  effect  of implementation strategy Giving Questions and Getting Answer (GQGA) towards biology learning achievement. This research held upon senior high school  student  of SMA  N  Banyudono in academic year 2011/2012. Giving Questions and Getting Answer (GQGA) was expected to be more effective rather than if use convensional method. All student of SMA N Banyudono had been chosen as a research population.Since, not all student was not attending biological class, hence, randomly, 2 clusters were  selected representing  the  control  class  (for where  the  experimental  treatment was not carried out) and the experimental class for where the Giving Questions and Getting Answer  (GQGA). Quasy-experimental  method was  designed to achieve  the stated research objectives following the quantitative paradigm used in this research. In addition, Randomized Subjects Posstest Only Control Group Design was used as a research design to facilitate  the  data  collection  procedures. The  data  were collected using  several  techniques  namely, questionnaire, posttest  with multiple  choice, observation tools and related document. The final obtained data were then analyzed using t- test method. The results of this research showed that the implementation of the strategy has significantly affected the biology learning achievement. It has been proven to have an impact towards cognitive, affective and psychomotor aspects. Keywords:      Giving Questions  and Getting Answer  (GQGA), Biology  Learning Achievement